2020
DOI: 10.1371/journal.pone.0228916
|View full text |Cite
|
Sign up to set email alerts
|

Construction and content validation of a measurement tool to evaluate person-centered therapeutic relationships in physiotherapy services

Abstract: This study sought to develop a tool for evaluating person-centered therapeutic relationships within physiotherapy services, and to examine the content validity of the same. Methods A mixed qualitative and quantitative study was performed in three distinct phases: 1) the items were generated based on a literature review and a content analysis of focus groups of patients and physiotherapists; 2) an e-Delphi survey process was performed based on three rounds to select and refine the proposed questionnaire; 3) two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…The individual item contribution to the factorial structure of the instrument is consistent with other studies [ 5 , 19 , 25 , 26 ]. More particularly, the most repeated questions in the literature (Questions 8, 9, 16, 17, 18 and 20), which explain most of the variance in the user’s satisfaction construct, belong to the information shared in the medical staff-patient relationship.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The individual item contribution to the factorial structure of the instrument is consistent with other studies [ 5 , 19 , 25 , 26 ]. More particularly, the most repeated questions in the literature (Questions 8, 9, 16, 17, 18 and 20), which explain most of the variance in the user’s satisfaction construct, belong to the information shared in the medical staff-patient relationship.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, some authors have identified factors similar to that included in the H-PTPS, such as Rodríguez Nogueira et al, who included a factor referred to as “environment” with items such as “I observe a lack of coordination between the team of professionals (physiotherapists, doctors, aids, administration staff, etc.) who attend me” [ 5 ]. In this sense, potential reasons for the lack of notable improvements in physical therapy patient outcomes and health expenditures could be related to traditional medical care models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations